2018
DOI: 10.1016/j.ihj.2018.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic studies targeting primary cardiovascular disease prevention in South Asia

Abstract: South Asia has experienced a 73% increase in healthy life years lost due to ischemic heart disease between 1990 and 2010. There is a lack of quality data relating to cardiovascular risk factors and disease from this region. Several observational and prospective cohorts in South Asia have been established in recent times to evaluate the burden of cardiovascular disease and their risk factors. The Prospective Rural Urban Epidemiology (PURE) study is the largest of these studies that has provided data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…A cross-sectional survey 9 reported an estimated prevalence of hypertension to be 26% in Pakistan, with a dominance of patients residing in the urban setting. In addition, Prospective Rural Urban Epidemiology (PURE) study 8 found the combined prevalence of hypertension in Pakistan, Bangladesh and India hovering around 40%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A cross-sectional survey 9 reported an estimated prevalence of hypertension to be 26% in Pakistan, with a dominance of patients residing in the urban setting. In addition, Prospective Rural Urban Epidemiology (PURE) study 8 found the combined prevalence of hypertension in Pakistan, Bangladesh and India hovering around 40%.…”
Section: Introductionmentioning
confidence: 99%
“…The study recommends that culturally sensitive interventions geared towards treating risk factors identified in these studies are needed to fully realize the true potential of these epidemiologic studies. 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average journey speed in the national capital is around 16 kmph while it is slightly higher in Mumbai, the financial capital of India. The growth in vehicular population is more than the growth of population in most of the Indian cities, and the annual growth generally ranges from 15 to 20% (Reddy and Balachandra 2010). As the urban population utilizes different transportation modes for undertaking daily journeys, the modal choice is influenced by a various set of factors comprising mainly of social, economic, physical, and human.…”
Section: Traffic Scenario Of Indian Citiesmentioning
confidence: 99%
“…Usage of two-wheelers and private cars are the most preferred, while walking and bicycles, which were once an important means of mobility, have taken a back seat. Motorcycles and private cars are generally preferred by people in the age group of 20 to 35 years, which forms nearly 60% of the population (Reddy and Balachandra 2010). The increasing usage of private means of transportation is an important factor that directly relates to the degradation of environmental quality and higher energy utilization.…”
Section: Traffic Scenario Of Indian Citiesmentioning
confidence: 99%